2018
DOI: 10.1128/aac.01520-18
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Carbapenemase-Producing Klebsiella pneumoniae with Chromosomally Carried bla NDM-1

Abstract: We report here Klebsiella pneumoniae strains carrying chromosomal blaNDM-1 in Thailand. The genomes of these two isolates include a 160-kbp insertion containing blaNDM-1, which is almost identical to that in the IncHI1B-like plasmid. Further analysis indicated that IS5-mediated intermolecular transposition and Tn3 transposase-mediated homologous recombination resulted in the integration of blaNDM-1 into the chromosome from an IncHI1B-like plasmid. The spread of this type of carbapenem-resistant Enterobacteriac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…Moreover, we demonstrated chromosomal integration of Group IncF plasmids in some E. coli isolates. Carbapenemase genes have been reported to be transmitted primarily through plasmid conjugation [4], and chromosomal integration has been reported in a limited number of strains [28]. In our study, three out of 135 E. coli isolates (2.2%) exhibited chromosomal integration of bla IMP−6 , which presumably occurred during the vast horizontal spread of pKPI-6.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Moreover, we demonstrated chromosomal integration of Group IncF plasmids in some E. coli isolates. Carbapenemase genes have been reported to be transmitted primarily through plasmid conjugation [4], and chromosomal integration has been reported in a limited number of strains [28]. In our study, three out of 135 E. coli isolates (2.2%) exhibited chromosomal integration of bla IMP−6 , which presumably occurred during the vast horizontal spread of pKPI-6.…”
Section: Discussionmentioning
confidence: 50%
“…In brief, I-CeuI endonuclease-digested PFGE followed by Southern blotting using probes for bla IMP−6 and 16S rRNA genes was performed to con rm the location of the bla IMP gene in three E. coli isolates E138, E300, and E302, as previously described [28].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we demonstrated chromosomal integration of group IncF plasmids in some E. coli isolates. Carbapenemase genes have been reported to be transmitted primarily through plasmid conjugation ( 4 ), and chromosomal integration has been reported in a limited number of strains ( 29 ). In our study, 3 of 135 E. coli isolates (2.2%) exhibited chromosomal integration of bla IMP-6 , which presumably occurred during the vast horizontal spread of pKPI-6.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates classified as chromosomal bla IMP carriers were further analyzed to identify the location of bla IMP . In brief, I-CeuI endonuclease-digested PFGE followed by Southern blotting using probes for bla IMP-6 and 16S rRNA genes was performed to confirm the location of the bla IMP gene in three E. coli isolates—E138, E300, and E302—as previously described ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chromosomally, both strains possess the fluoroquinolone and the fosfomycin resistance genes oqxB, oqxA, and fosA, but the ST14 isolate contained a penicillinase gene, bla SHV-28 , while the ST2497 isolates had a different penicillinase gene, bla SHV-182 . Phylogenetic analysis of the isolates showed that the ST14 isolate from the blood was closely related to strain KP67 (accession number AP018753.1), which also carries the bla NDM-1 gene that originated from Bangkok, Thailand (17), with 99.8% genome coverage and 98.7% pairwise identity, while the ST2497 isolates were genetically close to another strain, CRK0298 (accession number CP034039) originally identified from a body fluid in Ohio in 2015 with 95.1% genome coverage and 99.5% pairwise identity. However, no further information is available regarding the Ohio strain.…”
Section: Treatment and Outcomementioning
confidence: 99%